Disarming Canadians, and Arming them with Tolerance: Banning Firearms and Minimum Sentences to Control Violent Crime--An Essay on an Apparent Contradiction - Dumont, Helene (2001)
In an article published in French in 1997, the author offered reflections on feminism and criminal law that would allow for a better control of violent crime, without Parliament having to resort to excessively severe sentences. In this respect, she argued that there was no contradiction in supporting the radical ban of firearms in Canada, while opposing a minimum sentence of four years under the Firearms Act, which currently affects approximately ten serious Criminal Code offences. After setting out her position in favour of the disarmament of Canadians, the author argued that minimum sentences of four years were unconstitutional. Such sentences would constitute cruel and unusual punishment under section 12 of the Charter. They would also be contrary to one of the principles of fundamental justice guaranteed under section 7, which mandates proportionality between offences and sentences. Finally, the author argued that minimum mandatory sentences could not fulfill the objectives of general deterrence and of deserved retribution. On the contrary, they are ineffective in helping to reduce violent crime, and lead to arbitrary applications. In her epilogue to her 1997 article the author expresses her regret that the principle of proportionality has not been promoted as a constitutional principle of justice in the Momsey and the Latimer cases, and wonders if times are too hard for tolerance and moderate sentencing